Cataloguing Prof. Eudóxia M. Froehlich’s wet collection of land planarians (Platyhelminthes, Geoplanidae): a bounty of type specimens of 78 species - Ranelli, Beatriz Elias; de Freitas, Pedro M.; Carbayo, Fernando (Zootaxa, 2020)
Zoologist Prof. Eudóxia Maria Froehlich (1929*–2015†) kept an uncatalogued personal collection of land planarians in wet medium. We catalogued their contents. Glass jars contained a variable number of small vials, each with one or several labeled specimens. We transcribed the species names and field data, when available, written on card labels to a table. A total of 1772 vials in 80 jars, contained over 2700 specimens. Subsequently, we cross checked field data with that of the type specimens. As a result, we identified, with different degrees of certainty, type specimens of 78 species. These types compose a very significant potential source of additional morphological details of the species to conform with current standards in the taxonomy of the group.